CLEFT-Q SwePsych protocol: A prospective observational study to investigate the psychometric characteristics test-retest reliability, responsiveness, and interpretability of CLEFT-Q - Mia Stiernman; Kristina Klintö; Anna-Paulina Wiedel; Malin Schaar-Johansson; Måns Cornefjord; Björn Schönmeyr; Gudrun Stålhand; Mikael Korduner; Martin Bengtsson; Maria Mani; Malin Hakelius; Roshan Peroz; et al. (PLoS ONE, 2025)
Objectives Patient perceived benefit of treatment for cleft lip and/or palate is of great importance since it is central to development of cleft care. CLEFT-Q is a cleft-specific questionnaire on health-related quality of life. Test-retest reliability, aspects of responsiveness and interpretability are yet to be established for CLEFT-Q. This study aims to investigate these psychometric characteristics of CLEFT-Q. Methods To establish the test-retest reliability of CLEFT-Q, data will be collected repeatedly and independently at approximately 1-week intervals. Inclusion of approximately 50 patients is considered adequate for a test-retest study. To improve the interpretability of CLEFT-Q norm data from a control population of volunteers without a cleft will be collected. A total of approximately 210 participants will be included from schools, high-schools and universities. To test the responsiveness of CLEFT-Q, patients will answer selected subscales of CLEFT-Q, longitudinal anchor questions and perform global ratings of change before and after surgery. To ensure robust results, approximately 50 patients for each type of treatment will be recruited. If CLEFT-Q is found to be responsive, the pre- and postoperative difference in scores of CLEFT-Q will be compared with the change in objective measurements based on assessments by professionals in cleft care obtained in this study. To evaluate interpretability, results will be analysed to investigate the minimal important change using anchor-based, distribution-based and qualitative approach. Registration details This study is registered at ClinicalTrials.gov under the ID 2021-06993-01.